Improved Ability to Listen to Children of Group A in Al A'raaf Islamic Kindergarten Through Audio Visual Media - Karennina Cahya; Ruli Hafidah; Retnu Sipparamita (Golden Age: Jurnal Pendidikan Anak Usia Dini, 2020)
This study aims to improve listening skills through audio-visual media in to Children of group A in Al A'raaf Islamic Kindergarten Gentan, Baki, Sukoharjo. The subjects were children of 4-5 years age group TK Islam Al A’raaf kindergarten amounted to 25 children. Methods of data collection is done through observation, interview, and documentation.The data analysis technique performed a qualittative descriptive. Based on the results of discussion, it can be concluded that listening skills in children can be improved by audio-visual with a display of various types of stories. Children show improvement in answering simple questions given by the teacher regarding the contents of the story being aired as well as an increase in the average results of children's listening abilities.Initial average listening skills of students were 9% increased to 71% in the second meeting.Keywords : listening skills, audio-visual media , group A kindengarten